PUSAT MODE DI KOTA PONTIANAK DENGAN KONSEP CITY WALK - Rhisma Aulia Ahmad; Irwin Irwin; Yudi Purnomo (JMARS: Jurnal Mosaik Arsitektur, 2021)
The people of West Kalimantan Province have a great interest in fashion. This can be seen from the many facilities available to meet the needs of fashion and the emergence of young designers in the fashion sector, especially in Pontianak City. This of course must be balanced with education about the basics of fashion design knowledge and techniques in order to produce higher quality designers, and supported by marketing and promotion facilities to develop the creativity of fashion actors. The Fashion Center is an alternative to making all fashion activities carried out in one location, related to commercial activities, promotion, education and production to accommodate a place for fashion actors to work as well as interesting creations for visitors, especially in the Pontianak City area. The design process of the Fashion Center uses the J.C. Jones, who starts with an idea that is equipped with information, is then analyzed to produce concepts that match the initial idea and then evaluated. The concept in the design is semi-outdoor with interconnected spatial arrangement and placement of circulation paths. Provision of green open space around the circulation path.